Enamel subsurface caries-like lesions induced in human teeth by different solutions: A TMR analysis - Gouvêa, Daiana Back; Dos Santos, Nicole Marchioro; Pessan, Juliano Pelim [UNESP]; Jardim, Juliana Jobim; Rodrigues, Jonas Almeida (FapUNIFESP (SciELO), 2020)
This study assessed the effectiveness of models for developing subsurface caries lesions in vitro and verified mineral changes by transverse microradiography (TMR). Enamel blocks from permanent (n=5) and deciduous teeth (n=5) were submitted to lesion induction by immersion in demineralizing solutions during 96 h, followed by pH cycles of demineralization (de) and remineralization (re) for 10 days. Two de-/re solutions were tested. Demineralizing solution “A” was composed by 2.2 mM CaCl2, 2.2 mM KH2PO4, 0.05 M acetic acid, with pH 4.4 adjusted by 1 M KOH. Demineralizing solution “B” was composed by 2.2 mM CaCl2, 2.2 mM NaH2PO4, 0.05 M acetic acid and 0.25 ppmF, with pH 4.5 adjusted by 1M KOH. Solution “A” produced cavitated lesions in permanent teeth, whereas solution “B” led to subsurface lesions in deciduous teeth. Solution “B” was then tested in enamel blocks from permanent teeth (n=5) and subsurface lesions were obtained, so that solution “B” was employed for both substrates, and the blocks were treated with slurries of a fluoride dentifrice (1450 ppm F, as NaF, n=5) or a fluoride-free dentifrice (n=5). Solution “B” produced subsurface lesions in permanent and primary teeth of an average (±SD) depth of 88.4μm (±14.3) and 89.3μm (±15.8), respectively. TMR analysis demonstrated that lesions treated with fluoride-free dentifrice had significantly greater mineral loss. This study concluded that solution “B” developed subsurface lesions after pH cycling, and that mineral changes were successfully assessed by TMR.
Keywords: Demineralization; Dental caries; PH cycling; Remineralization; TMR